2015
DOI: 10.3389/fnhum.2015.00654
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation over the Medial Prefrontal Cortex and Left Primary Motor Cortex (mPFC-lPMC) Affects Subjective Beauty but Not Ugliness

Abstract: Neuroaesthetics has been searching for the neural bases of the subjective experience of beauty. It has been demonstrated that neural activities in the medial prefrontal cortex (mPFC) and the left primary motor cortex (lPMC) correlate with the subjective experience of beauty. Although beauty and ugliness seem to be semantically and conceptually opposite, it is still unknown whether these two evaluations represent extreme opposites in unitary or bivariate dimensions. In this study, we applied transcranial direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 45 publications
(71 reference statements)
1
29
2
Order By: Relevance
“…Moreover, no brain stimulation study has so far assessed whether premotor regions are also involved in aesthetic valuation of artworks. Some preliminary evidence for the involvement of the primary motor cortex in aesthetic valuation of artworks can be found in the work of Nakamura and Kawabata (2015), although simultaneous stimulation of prefrontal and motor cortices as used in this former study prevents the drawing of clear conclusions about the unique contribution of the two targeted regions. Other studies (Battaglia et al 2011; Jola and Grosbras 2013) measured MEPs as an index of motor cortex excitability while viewing paintings or dance, but they did not assess whether MEPs were affected by subjective preference for the viewed stimuli.…”
Section: Summary and Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Moreover, no brain stimulation study has so far assessed whether premotor regions are also involved in aesthetic valuation of artworks. Some preliminary evidence for the involvement of the primary motor cortex in aesthetic valuation of artworks can be found in the work of Nakamura and Kawabata (2015), although simultaneous stimulation of prefrontal and motor cortices as used in this former study prevents the drawing of clear conclusions about the unique contribution of the two targeted regions. Other studies (Battaglia et al 2011; Jola and Grosbras 2013) measured MEPs as an index of motor cortex excitability while viewing paintings or dance, but they did not assess whether MEPs were affected by subjective preference for the viewed stimuli.…”
Section: Summary and Discussionmentioning
confidence: 86%
“…These sites were targeted in light of prior fMRI evidence showing that the vmPFC responds more to preferred paintings, whilst the motor cortex seems to respond more to artworks perceived as ugly, possibly reflecting motor preparation to avoid the ugly or aversive stimulus (Kawabata and Zeki 2004; Ishizu and Zeki 2011). In line with this evidence, Nakamura and Kawabata (2015) hypothesized that enhancing excitability in one of these two regions while concurrently inhibiting excitability of the other region would have affected beauty and ugliness evaluations. Participants performed beauty and ugliness rating tasks before and after the application of 2 mA tDCS (stimulation was delivered for approximately 15 min).…”
Section: Aesthetic Preference For Bodies and Paintings: Involvement Omentioning
confidence: 93%
See 1 more Smart Citation
“…It is perhaps not surprising, therefore, that regardless of source, it correlates with activity in field A1 of mOFC [Ishizu and Zeki, 2011], a region of the emotional brain which has been generally associated with pleasure and reward (e.g., O'Doherty et al, 2001); activity in it has been shown to correlate parametrically with the declared intensity of the experience of beauty derived from a variety of stimuli, such as faces, colors, motion, paintings, music, architectures, moral judgments, and mathematical equations [Ikeda et al, 2015;Ishizu and Zeki, 2011;Kawabata and Zeki, 2004;Kuhn and Gallinat, 2012;O'Doherty et al, 2003;Zeki and Stutters, 2012;Tsukiura and Cabeza, 2011;Vartanian et al, 2013 for a meta-analysis; Zeki et al, 2014] though apparently not from the performing (dance) arts [e.g., Calvo-Merino, et al, 2008;Cross et al, 2011]. Moreover, a recent study has reported an increase in aesthetic ratings of visual stimuli [Nakamura and Kawabata, 2015] following the application of anodal transcranial direct current stimulation to the mOFC, presumably because of enhanced neural activity within it.…”
Section: Discussionmentioning
confidence: 99%
“…Following the reductionist approach of science, the experiments typically analyze the perception of one isolated stimulus. In experimental aesthetics, for instance, the prototypical study shows one image at a time and observers report how beautiful or pleasing they find it (e.g., Cotter, Silvia, Bertamini, Palumbo, & Vartanian, 2017;Graf & Landwehr, 2017;Marin & Leder, 2016;Nakamura & Kawabata, 2015;Savazzi et al, 2014). In everyday life, however, we enjoy the pleasantness of any kind of object (e.g., the attractiveness of a face, the taste of popcorn, the sound of music) in the context of others (e.g., other faces in a crowd, the movie theater, street noise).…”
Section: Introductionmentioning
confidence: 99%